The Use Of Quizizz And Youtube To Improve The Accounting Literacy Of Vocational Students During Industrial Work Practices - Muaddab, Hafis (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: The purpose of this study is to identify resistance to change and recommend one or more methods to manage that resistance. Group and Google Classroom media, making financial accounting subjects easy for students to understand. Design/Methode/Approach: This research used quantitative methods through descriptive data analysis techniques and experimental approaches. Conducted experimental research in the form of Pre-Experimental Designs with One-Group Pretest-Posttest. The sample used in this research was 27 students from class XI AK 1, using a purposive sampling technique. Data analysis was carried out using the Wilcoxon test and N-Gain test. Conducted online learning during fieldwork practices of second-year vocational high school. Research Finding: Important research results found that the use of Quizizz media was quite effective in learning accounting material. Wilcoxon test data concluded that the Ho result was declared correct and Ha was rejected with Asymp. Sig. (2-tailed) 0.001 < 0.05. The N-gain test found that the N-gain analysis results were at 58.4921% which was concluded to be quite effective. Statically the findings showed that Quizizz and YouTube keep students motivated, and make them pay attention during online learning. Theoretical contribution/Originality : The study adds to the discourse on the usefulness of social platforms in vocational education learning. Practitioner / Policy implication : The study adds to the discourse on the usefulness of Quizizz and YouTube platforms in vocational education settings during fieldwork practices. Research limitation : As this paper focuses on one school, the findings may not be generalizable. In addition, the relatively small sample size could be another limitation.